2019
DOI: 10.1002/jcc.25808
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on photophysical properties of a series of functional pyrimidine‐based organic light‐emitting diodes emitters presenting thermally activated delayed fluorescence

Abstract: Issue concerning accurate prediction of the reverse intersystem crossing rate (kRISC) is critical for developing novel efficient thermally activated delayed fluorescence (TADF) materials. In this contribution, the kRISC rates from the lowest excited triplet T1 state to the lowest excited singlet S1 state were evaluated for five donor‐π‐acceptor‐type pyrimidine‐based TADF emitters using the semiclassical Marcus theory. Both the singlet‐triplet energy difference (ΔEST) and spin–orbit coupling (V) between the S1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 80 publications
0
16
0
1
Order By: Relevance
“…The presence of a methyl group in the structure of dyes 22b and 23c triggers a slightly blue-shifted emission and a large increase of their PLQY without modifying significantly DE ST nor delayed fluorescence lifetimes. Compounds 22a, 22b, 23a and 23c have also been investigated in a recent theoretical work by Zhu et al 69 Using a semi-classical approach and TD-DFT, they estimated both the SOC and DE ST , granting access to the theoretical reverse intersystem crossing rate constant, k RISC . Calculated k RISC are in good agreement with the experimental measurements, ranging from 1.22x10 5 s -1 for 22b to 2.30x10 6 s -1 for 23a.…”
Section: Dihydroacridine (Acridan) Substituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a methyl group in the structure of dyes 22b and 23c triggers a slightly blue-shifted emission and a large increase of their PLQY without modifying significantly DE ST nor delayed fluorescence lifetimes. Compounds 22a, 22b, 23a and 23c have also been investigated in a recent theoretical work by Zhu et al 69 Using a semi-classical approach and TD-DFT, they estimated both the SOC and DE ST , granting access to the theoretical reverse intersystem crossing rate constant, k RISC . Calculated k RISC are in good agreement with the experimental measurements, ranging from 1.22x10 5 s -1 for 22b to 2.30x10 6 s -1 for 23a.…”
Section: Dihydroacridine (Acridan) Substituentsmentioning
confidence: 99%
“…21,22 Although more complex firstprinciple approaches, based on (spin)-vibronic models, have been recently proposed to explore the TADF mechanism, 10,23,24 the semi-classical theory remains a popular tool to rationalize and predict the impact of chemical substitution and establish structure-TADF properties relationships. 25,26,27,28 Noteworthy, even so DFT and TD-DFT are first-principles approaches, they still face challenges related to the unknown exact expression of the exchange-correlation kernel, 29,30 that might for instance lead to low-lying spurious CT states, and even state-of-the art TD-DFT solvation models may not reach chemical accuracy. 31 The diazine derivatives are six-membered aromatic heterocycles comprising of two nitrogen atoms in their structure.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the HFX amount plays a major role in the performance of global hybrid functionals. Predictions for various molecular properties, such as singlet–triplet energy gap, electronic coupling, electronic excitation, dipole/quadrupole moments, and reduction potential are affected by HFX. E * ,Δ could be decomposed into E 0 , E fluo , and Δ, and their prediction quality could be tuned with HFX.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous mechanism investigations support experimental luminescence phenomena and predict the properties of TADF molecules. [31][32][33][34][35][36][37][38][39][40][41][42][43] For example, the Shuai group investigated the TADF mechanism of 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene and found that the rotation of the Cz ligand between two cyano groups leads to the interconversion between S 1 and T 1 . The intramolecular steric hindrance hinders the nonradiative transition of S 1 -S 0 , which in turn enhances the fluorescence.…”
Section: Introductionmentioning
confidence: 99%